2018
DOI: 10.1016/j.dld.2017.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Exercise has the guts: How physical activity may positively modulate gut microbiota in chronic and immune-based diseases

Abstract: Please cite this article as: Codella Roberto, Luzi Livio, Terruzzi Ileana.Exercise has the guts: how physical activity may positively modulate gut microbiota in chronic and immune-based diseases.Digestive and Liver Disease https://doi.org/10.1016/j.dld. 2017.11.016 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(111 citation statements)
references
References 123 publications
2
103
0
6
Order By: Relevance
“…Multiple questions remain. Many of these relate to underlying and potentially novel mechanisms that need to be investigated in humans such as the role of the microbiota (Codella, Luzi, & Terruzzi, 2018) and exosomes (Ge, Xie, Xiao, & Li, 2019, Li et al., 2019) during exercise in chronic inflammatory disorders, and to the appropriate dose of exercise for β‐cell health in different populations. Studies conducted in a non‐diabetic population suggest a linear relationship between exercise dose and β‐cell function (Malin et al., 2013); however, studies in T2D suggest that long duration–higher intensity exercise is less beneficial than moderate duration and intensity of exercise (Slentz et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple questions remain. Many of these relate to underlying and potentially novel mechanisms that need to be investigated in humans such as the role of the microbiota (Codella, Luzi, & Terruzzi, 2018) and exosomes (Ge, Xie, Xiao, & Li, 2019, Li et al., 2019) during exercise in chronic inflammatory disorders, and to the appropriate dose of exercise for β‐cell health in different populations. Studies conducted in a non‐diabetic population suggest a linear relationship between exercise dose and β‐cell function (Malin et al., 2013); however, studies in T2D suggest that long duration–higher intensity exercise is less beneficial than moderate duration and intensity of exercise (Slentz et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Human gut microbiota is composed by trillions of symbiotic microorganisms which play important roles in maintaining intestinal homeostasis and modulating the immune system. Physical exercise can restore intestinal health favoring beneficial modifications of gut microbiota [79,80]. It has been shown that exercise contributes to increase microbial diversity in the presence of HFD, reduces inflammation and increases antioxidant enzymes [81].…”
Section: Physical Exercise and Changes In Gut Microbiota In Obese Indmentioning
confidence: 99%
“…In the gut several bacteria synthesize vitamins such as vitamin K, folic acid or thiamine [80]. Recently, we found that exercise increased the levels of two metabolites of vitamin B6 salvage pathway (pyridoxal 5 -phosphate, pyridoxamine 5 -phosphate) [85].…”
Section: Physical Exercise and Changes In Gut Microbiota In Obese Indmentioning
confidence: 99%
“…Other modifying factors ( Figure 1 ) include psychological stress 33,34 , physical activity 35 , tobacco use 36 , alcohol consumption 37 , and antibiotic exposure 38, 39,40 . In one population-level analysis of gut microbiome variation, 69 factors were shown to correlate with microbiome community variation, with stool consistency emerging as the most influential covariate 41 .…”
Section: Introductionmentioning
confidence: 99%